2023
DOI: 10.1002/wat2.1666
|View full text |Cite
|
Sign up to set email alerts
|

The effects of household water insecurity on child health and well‐being

Steven J. Rhue,
Giulia Torrico,
Chioma Amuzie
et al.

Abstract: We extend the conceptualization of the social and health burdens of household water insecurity on children beyond the traditional narrow lens of microbiological pathogens and diarrhea. The global burden of disease associated with water insecurity has traditionally focused on diarrheal disease as the most significant driver of infant and child mortality. However, there are many other pathways through which children experience adverse health and social consequences from inadequate or unsafe household water. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 148 publications
0
2
0
Order By: Relevance
“…Adetayo et al (2019) found that approximately 60% of respondents perceived water scarcity to have a negative impact on their livelihoods, while the current study illustrates respondents' concerns over the impacts of water scarcity on economic stability, health satisfaction, and overall quality of life. Rhue et al (2023) explored the effects of household water insecurity on child health and well-being, extending the scope beyond microbiological pathogens to encompass various health impacts. This broader perspective aligns with the current study's focus on the multifaceted repercussions of water scarcity on household well-being, including economic, social, and health-related aspects.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Adetayo et al (2019) found that approximately 60% of respondents perceived water scarcity to have a negative impact on their livelihoods, while the current study illustrates respondents' concerns over the impacts of water scarcity on economic stability, health satisfaction, and overall quality of life. Rhue et al (2023) explored the effects of household water insecurity on child health and well-being, extending the scope beyond microbiological pathogens to encompass various health impacts. This broader perspective aligns with the current study's focus on the multifaceted repercussions of water scarcity on household well-being, including economic, social, and health-related aspects.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Waterborne diseases claim more lives annually than all forms of violence or warfare combined. Indeed, infants and young children are more likely to die from waterborne diseases due to poor water sanitation than from conflicts or violence [ 27 ]. Therefore, the interconnection between water issues and climate change is inseparable in terms of enhancing human health, nutrition, and the sustainability of agriculture.…”
Section: The Sustainability Of Agriculture and Nutritionmentioning
confidence: 99%
“…The assessment and management of drinking water quality have emerged as crucial fields, addressing the need for continuous monitoring and maintenance of water supplies. Numerous research articles highlight the risks associated with contaminated drinking water, including the transmission of waterborne diseases, adverse health effects, and potential long-term consequences on the overall wellbeing of individuals and communities [9][10][11]. Consequently, the importance of maintaining high standards of drinking water quality is widely recognized in the scientific community as a fundamental necessity for safeguarding public health and promoting sustainable development.…”
Section: Introductionmentioning
confidence: 99%